Radio Komunitas di Indonesia: ‘New Brechtian Theatre’ di Era Reformasi? - Edwin JurriÃ«ns (Antropologi Indonesia, 2003)
This article is about community radio in Indonesia. This type of radio developed as an alternative to both public radio and commercial radio after the fall of Soeharto in 1998. Two important features of community radio are that it provides all community members with equal access to information, and also enables them to participate actively in management and production. Both features enhance people's self-awareness and sense of belonging to a community. This article compares the way in which community radio creates communal feelings with Bertolt Brecht's ideas on theatre and radio, and Walter Benjamin's theory of mass media. In the second part of the article, the conceptual tools generated by this comparative framework are used for the discussion of the ideas and practices of community radio practitioners in Central Java. The stations discussed comprise two types of community radio: one based on geographical or professional grounds, the other tied to the interests of students at university campuses (so-called campus radio). The theoretical discussions of community radio as well as the description of the Central Javanese radio stations make it clear that community radio has a democratic right and duty to exist in Indonesian society, as it enables social groups to express themselves without interference of other parties, and contributes to the variety of the Indonesian media scene.